2018
DOI: 10.3892/etm.2018.6330
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin protects PC12 cells from ERS‑induced apoptosis in OGD/R injury via activation of the PI3K/AKT pathway

Abstract: Nobiletin (NOB) possesses multiple pharmacological effects, but its anti-apoptotic property has acquired a great deal of attention. Endoplasmic reticulum (ER) stress (ERS)-induced apoptosis acts as the pivotal aetiology in neuronal oxygen-glucose deprivation and reoxygenation (OGD/R) injury. The aim of this study focused on whether NOB exerts neuro-protective effects on OGD/R injury by repressing ERS-induced apoptosis. The PC12 neuronal cell line was subjected to 4 h OGD and 24 h reoxygenation following NOB tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…ER stress was reported to be regulated by three canonical signaling pathways: PERK‐eIF2α‐ATF4‐CHOP, IRE1‐XBP1, and ATF6‐ERAD, in various issues . Further, several studies have reported that the PERK‐eIF2α‐ATF4‐CHOP signaling pathway plays an essential role in ER stress‐induced apoptosis, especially in neuronal issues including spinal cord injury, subarachnoid hemorrhage injury, and cerebral ischemia injury . In the present study, our data indicated consistent involvement of PERK‐eIF2α‐ATF4‐CHOP in ER stress‐induced apoptosis in CDI generated by PEL surgery.…”
Section: Discussionsupporting
confidence: 83%
“…ER stress was reported to be regulated by three canonical signaling pathways: PERK‐eIF2α‐ATF4‐CHOP, IRE1‐XBP1, and ATF6‐ERAD, in various issues . Further, several studies have reported that the PERK‐eIF2α‐ATF4‐CHOP signaling pathway plays an essential role in ER stress‐induced apoptosis, especially in neuronal issues including spinal cord injury, subarachnoid hemorrhage injury, and cerebral ischemia injury . In the present study, our data indicated consistent involvement of PERK‐eIF2α‐ATF4‐CHOP in ER stress‐induced apoptosis in CDI generated by PEL surgery.…”
Section: Discussionsupporting
confidence: 83%
“…However, due to the narrow therapeutic window, patients with AIS may fail to gain the benefits of acute treatments (Nogueira et al, 2018). Cerebral ischemia/reperfusion (I/R) injury rapidly triggers different types of programmed cell death in neurons, such as apoptosis, autophagy and programmed necrosis, and this injury is inevitable and irreversible (Li et al, 2018). Therefore, it is vital to increase the resistance of neurons to ischemic conditions in the early stage of AIS when mildly injured neurons have not entered the process of apoptosis or necrosis (Ovesen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The OGd/R model has been commonly recognized as the in vitro model simulating cIRI (44)(45)(46). First, the complete culture medium was discarded, and the cells were washed twice with 1X PBS.…”
Section: In Vitro Model Of Oxygen-glucose Deprivation/reoxygenation (mentioning
confidence: 99%